1995
DOI: 10.1136/bmj.310.6973.158
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health education interventions for young people: a methodological review

Abstract: * The perinatal necropsy rate in most of the United Kingdom fails to reach the minimum target of 75% * The quality of many perinatal postmortem examinations is considered poor * Present findings show that necropsy discloses the main cause of death in 18% of perinatal and infants deaths and other new information in a further 8% of deaths * Clinically important information is more likely to emanate from a good quality necropsy * Clinicians should take a more positive attitude towards postmortem examinations net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(123 citation statements)
references
References 29 publications
0
118
0
5
Order By: Relevance
“…25 It was found that proactive screening for chlamydia in women and men under 25 years of age, using homecollected specimens, was feasible and acceptable, but screening was not found to be cost-effective. A number of research recommendations were made to fill gaps in the evidence base, including a randomised controlled trial (RCT) of chlamydia screening.…”
Section: Cost-effectiveness Of Behavioural Interventions To Reduce Stismentioning
confidence: 99%
See 1 more Smart Citation
“…25 It was found that proactive screening for chlamydia in women and men under 25 years of age, using homecollected specimens, was feasible and acceptable, but screening was not found to be cost-effective. A number of research recommendations were made to fill gaps in the evidence base, including a randomised controlled trial (RCT) of chlamydia screening.…”
Section: Cost-effectiveness Of Behavioural Interventions To Reduce Stismentioning
confidence: 99%
“…The two models developed for chlamydia screening provided very different estimations of cost-effectiveness, even though both used similar modelling methods (£1350 112 versus £26,000 25 per major outcome avoided). The differences between these models were due to differences in assumptions and data values, and these differences far exceed the difference shown comparing the results from static and dynamic models (Welte and colleagues 110 ).…”
Section: Low and Colleaguesmentioning
confidence: 99%
“…Over the year program implementers have consistently ignored the role of psychosocial perspectives of program beneficiaries [1][2][3]. A growing body of literature suggests that translating psychological theories into practice can help in implementing more effective HIV intervention programs [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Therefore, to translate knowledge about HIV into risk-reducing behaviours, prevention initiatives must be able to personalise the risk of HIV infection, the seriousness of becoming infected, the benefits of practising safer sex, and the skills learned so that there is self-efficacy to practise them. [9] The AOI course is designed to reflect these theories by incorporating into the curriculum activities intended to influence specific beliefs towards safer sexual practices.…”
Section: Discussionmentioning
confidence: 99%